Avaliação de impactos da Bolsa-Escola sobre a saúde de crianças e adolescentes: efeitos de alocação intrafamiliar - Machado, Renata Ferraz de Toledo (2008)
Many conditional cash transfer programs are obtaining enormous internacional approval. In Brazil, the Bolsa Família program, created in 2003, has been expanded continually. Depite of that many impact evaluation studies have shown that their impact on promoting more investiment in education have been small. This study aims to analyse if the Bolsa Escola program has had an positive impact on another dimension of human capital – the health. There are no evidence that the Bolsa Escola program has had na positive impact on health of children and adolescents. Also there are no evidence that there is a difference in the impact of the program on boys and girls living in the same family.